Food poisoning due to mushroom consumption during the COVID-19 pandemic in Bantul Regency, October 2021 - Puspitarani, Fitriana (BKM Public Health and Community Medicine, 2021)
Objective: This study aims to determine the magnitude of the problem of extraordinary events (KLB) of food poisoning due to mushroom consumption, including the factors that influence the occurrence of these outbreaks, so that recommendations can be made to avoid similar events in the future. Method: Epidemiological descriptive study with definitions Cases were all people who experienced symptoms of vomiting, headache, and diarrhea after consuming wild mushrooms in their home environment in October 2021. Interviews were conducted using a structured questionnaire to the population at risk. Environmental observations are also carried out to see the environmental risks in which wild mushrooms grow. Vomit samples were collected for laboratory examination, but food samples were not obtained. Results: Eight people consumed mushrooms in 14 days in Bambanglipuro and Bantul districts with an attack rate of 100%. Symptoms that can be identified are vomiting (100%), nausea (75%), cold sweats (37.5%), and dizziness (37.5%). The incubation period ranged from 1 hour 30 minutes to 4 hours with a median of 2 hours 45 minutes. Consumption of mushrooms is very risky for the incidence of illness with suspicion leading to mushroom toxin based on the incubation period, symptoms, and food characteristics. Suspicion leads to the features of the mushrooms consumed containing toxins because they grow on the ground close to livestock or manure. It is necessary to carry out socialization and health promotion related to how to identify poisonous mushrooms and monitor the local area for some time to come.